PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PT. Sun Star Motor Kudus) - Anhar Royyan, 13.05.51.0052; Waru wu, Penunjang (Students' Journal of Economic and Management, 2018)
Abstract - The object of research done at PT. Sun Star Motor Kudus. This study aims to analyze the influence of motivation, work environment and work discipline on the performance of employees of PT. Sun Star Motor Kudus. The population is all employees of the marketing division active in PT. Sun Star Motor Kudus consisting of 43 people. The sampling technique was done by using census or saturated samples because all study populations were sampled. Methods of data analysis using linear regression. Test results obtained that there is a positive and significant effect of work motivation on employee performance, there is a positive and significant impact of work environment on employee performance. And there is a positive and significant influence of work discipline on employee performance.Keywords: motivation, work environment, work discipline and employee performance.